Permasalahan yang Dihadapi Siswa SD Negeri 1017766 Bandar Setia Dalam Pembelajaran Volume Bangun Ruang - Suci Rahmadani Br Sinurat, Putri; Nurhudayah, Nurhudayah; Simanullang, Patricia; Sinambela, Destrina; Aulya Sagala, Thesa (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
The study is conducted using qualitative research methodology which involves observing, conducting interviews, and analyzing documents to collect data. The findings revealed that students struggled with comprehending the concept, formula, and calculation of the volume of three-dimensional objects. The challenges are a result of various factors, primarily the students' limited grasp of fundamental mathematical concepts. Improper instructional techniques. Insufficient learning materials utilized. Students are not provided with enough practice questions. Researchers suggest that teachers should incorporate more engaging and diverse teaching strategies, utilizing a range of techniques.